A mobile game‐based app to facilitate learners' motivation and achievement in learning Chinese reading activities: An individual differences perspective. (9th June 2022) - Yang, Jie Chi; Kuo, Wen‐Chi
Abstract: Background: Digital game‐based learning (DGBL) has been shown to be an effective strategy for promoting learning motivation. However, a lack of attention has been paid to investigating the effects of individual differences on elementary students' reading motivation and in‐gaming achievements in DGBL. Objectives: This study developed an educational mobile game to facilitate learners' reading activities, and investigated how prior knowledge and gaming experience affected learners' reading motivation, gaming motivation, perceptions and in‐game achievements. Methods: A total of 53 third to fifth grade elementary school students participated in this study, and were divided into the high prior knowledge (HPK)/low prior knowledge (LPK) and the high gaming experience (HGE)/low gaming experience (LGE) groups. Results and Conclusions: The HPK learners had higher reading motivation, perceptions, gaming and social achievements than the LPK learners, whereas they had similar gaming motivation and reading achievements. In addition, the HGE learners had lower reading motivation, reading and gaming achievements than the LGE learners, whereas they had similar gaming motivation, perceptions and social achievements. Moreover, correlational results showed that similarities and differences were observed between the HPK/LPK and HGE/LGE learners. Implications: The findings of this study suggest that learners' prior knowledge and gaming experience play influential roles in reading motivation, gaming motivation, perceptions and in‐game achievements. A framework is proposed for researchers or game designers to develop personalized DGBL systems to accommodate the HPK/LPK and HGE/LGE learners' individual needs or preferences in DGBL. Lay Description: What is already known about this topic: Reading motivation is a critical factor influencing reading performance. Students have difficulties developing reading skills due to a lack of reading motivation, and therefore need additional support. DGBL has been shown to be an effective strategy for promoting learning motivation. Relevant empirical research investigating the impact of individual differences on reading in DGBL is scarce. What this paper adds: A mobile game‐based reading app was developed to facilitate elementary students' reading activities. This study provides understandings of the impact of prior knowledge and gaming experience on reading motivation, gaming motivation, perceptions and in‐game achievements in DGBL. The HPK learners had higher reading motivation, perceptions, gaming and social achievements than the LPK learners, whereas they had similar gaming motivation and reading achievements. The HGE learners had lower reading motivation, reading and gaming achievements than the LGE learners, whereas they had similar gaming motivation, perceptions and social achievements. Implications for practice and/or policy: Educators should consider adopting DGBL to facilitate students' reading activities. Prior knowledge and gaming experience play influential roles in reading motivation, gaming motivation, perceptions and in‐game achievements. Learners' prior knowledge and gaming experience should be taken into account when designing learning activities in DGBL. A personalized DGBL system should be developed to accommodate the needs and preferences of the HPK/LPK and HGE/LGE learners.